Field‐Effect Biosensors for On‐Site Detection: Recent Advances and Promising Targets. Issue 20 (8th September 2017) - Choi, Jaebin; Seong, Tae Wha; Jeun, Minhong; Lee, Kwan Hyi
Abstract: There is an explosive interest in the immediate and cost‐effective analysis of field‐collected biological samples, as many advanced biodetection tools are highly sensitive, yet immobile. On‐site biosensors are portable and convenient sensors that provide detection results at the point of care. They are designed to secure precision in highly ionic and heterogeneous solutions with minimal hardware. Among various methods that are capable of such analysis, field‐effect biosensors are promising candidates due to their unique sensitivity, manufacturing scalability, and integrability with computational circuitry. Recent developments in nanotechnological surface modification show promising results in sensing from blood, serum, and urine. This report gives a particular emphasis on the on‐site efficacy of recently published field‐effect biosensors, specifically, detection limits in physiological solutions, response times, and scalability. The survey of the properties and existing detection methods of four promising biotargets, exosomes, bacteria, viruses, and metabolites, aims at providing a roadmap for future field‐effect and other on‐site biosensors. Abstract : On‐site biosensors offer great promise in immediate and cost‐effective analysis of field samples compared to immobile biosensors. Field‐effect biosensors are promising candidates due to their unique sensitivity, manufacturing scalability, and integrability with computational circuitry. This report summarizes the challenges for on‐site detection, current literature on field‐effect biosensors, and attractive targets for future on‐site biosensors.